The Analysis of Students’ Mental Models Using Macromedia Flash-Based Learning Media on Molecular Shapes Lesson - Siregar, Erlina Azmi; Kurniawati, Yenni (Universitas Negeri Semarang, 2022)
The profile of studentsâ€™ mental model was very needed to know student successes and difficulties in describing macroscopic, submicroscopic, symbolic representation as the characteristics of chemistry. This research aimed at analyzing the profile of studentsâ€™ mental model of experimental and control groups, and knowing the effect of Macromedia Flash based learning media toward studentsâ€™ mental model at the tenth grade of MIA.Â This research was conducted in the Academic Year of 2019/2020 at State Senior High School 1 Pekanbaru on Molecular Shapes lesson. It was Mixed Method Research integrating qualitative and quantitative researches with explanatory design. There were 20 students as the samples selected by using Simple Random sampling technique.Â Instruments used in this research were two-tier diagnostic test and interview to strengthen the data obtained. The results of analyzing the data showed that the profile of studentsâ€™ mental model of experimental group using Macromedia Flash based learning media overall had 70% intact mental model and 30% alternative mental model, the control group students had 37% intact mental model and 63% alternative mental model.Â The research findings also showed that there was an effect of Macromedia Flash based learning media toward studentsâ€™ mental model.Â The result of hypothesis testing that SPSS was used to help showed sig. (2-tailed) 0.000, it meant that Ha was accepted and H0 was rejected. Â